Synonyms of the Noun kaimietis in the Contemporary Lithuanian Language - Kvašytė, Regina; Župerka, Kazimieras (Acta humanitarica academiae Saulensis, 2025)
Earlier, dictionaries of the Lithuanian language would record only one entry of the meaning of the noun kaimietis, -ė (‘a male / female villager’ in Lithuanian): “a village inhabitant”. Presently, the Dictionary of the Literary Lithuanian Language (Lith. Bendrinės lietuvių kalbos žodynas) indicates another meaning of the word: “pejorative meaning – an uneducated, of bad taste, etc. person who not necessarily comes from a village”. Acknowledging the latter meaning, it remains stating that kaimietis (as a dominant) falls not only to the row of synonyms with the concept “a village man”, but also to the row of similar words (synonymous) bearing a pejorative meaning. Therefore, it is purposeful to review the extended synonymy of the noun kaimietis. The dictionaries of synonyms display the most characteristic synonyms of the first meaning: sodietis (‘a homestead peasant’) and valstietis (‘a peasant’). The word valstietis is included in the row of synonyms characterising the notion “a village man”’, with reference to “a word with a distant meaning”; its definition in the dictionary is “the one who is engaged with the earthwork, agriculture work”. Such definition allows the row of synonyms žemdirbys (‘an agriculturalist’) (as a dominant) joining the row of synonyms of kaimietis meaning “a village inhabitant”: laukininkas (‘a field peasant’), ūkininkas (‘a farmer’), etc.; valstietis is the link between these two rows of synonyms. The second row of synonyms with a similar meaning to that of kaimietis would comprise prastuolis (‘a lowbrow’), prasčiokas (‘a hick’); also, outside the limits of the literary language, it includes a barbarism mužikas (‘a kern’), a jargon word runkelis (‘a person as mindless as a beetroot’). The article maintains a broad notion, meaning, connotation and use of synonyms of the noun kaimietis, -ė; thus, the following words are compared: sodietis; valstietis; žemdirbys, laukininkas, ūkininkas, prastuolis, prasčiokas, mužikas; runkelis. The material was collected from all texts of different styles presented in the Corpus of the Contemporary Lithuanian Language (Lith. Dabartinės lietuvių kalbos tekstynas), also from other texts of the contemporary Lithuanian language.